Perancangan Media Interaktif Pengenalan Gamelan Selonding Berbasis Android: Penelitian Penciptaan Seni dari I Nyoman Agus Suarya Putra dengan,I Putu Gede Artika Putra - I Nyoman Agus Suarya Putra (Lembaga Penelitian Pengembangan dan Pengabdian Kepada Masyarakat STMIK Asia Malang, 2020)
Technology has an important role in human life. Humans are given the ease to do and complete activities to be more effective and efficient. In the next life, there was a shift in social activities to further introduce the community to support cultural preservation. The design of an information media about the local culture in technology can be used as a form of effort in the background of the nation's cultural assets so that it can be recognized by the wider community. Interactive media design for introduction of the selonding gamelan as one of the Hindu cultural heritage in Bali. By introducing the culture of megamelan selonding, it is hoped that it can make the community more familiar with preserving culture based on local wisdom. So an Android-based media design is very important to be designed and directly proportional to the development of science and technology in society. One of them utilizes Android-based smartphone technology as a medium to introduce selonding gamelan to the public. In this study the design and manufacture of interactive media is based on the existing instruments in the selonding gamelan. Making an interactive media introduction to Android-based gamelan selonding is expected to be a medium for preserving Balinese culture and to attract the interest of young people in learning selonding gamelan. After the implementation of interactive media, the Likert scale method is tested, the testing is carried out with the play process and the functions that exist on the interactive media. The results of the test are in line with expectations and on their respective functions.